EPIDEMIOLOGY AND STATISTICS OF UNCOMPLICATED COMPESSION FRACTURES OF THE SPINE IN CHILDREN (A LITERATURE REVIEW) - O. O. Sarukhanjan; N. V. Teleshov (Неотложная медицинская помощь, 2016)
ABSTRACT. Traumatic injury of spine vertebra in children is an actual problem of modern traumatology which is actively being discussed in literature. Recently, the frequency of such registered traumas has increased considerably. Primary diagnostics of uncomplicated traumas in spinal vertebra in children has considerable difficulties which are determined by objective reasons, and is characterized by a high percentage of mistakes. The clinical presentation, diagnostics and treatment of stable injuries of spinal vertebra in children need further studies.